2020
DOI: 10.3390/ijerph17103660
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of an Assessment Tool for Developmental Dyslexia in Chinese Children

Abstract: Developmental dyslexia (DD) is a common neurobehavioral disorder in children. It refers to the phenomenon in which children with normal intelligence lag significantly behind their peers in reading ability. In China, there is no unified standard for the assessment of dyslexia due to the use of simplified and traditional Chinese characters in different regions. This study was aimed at analyzing the reliability and validity of the self-developed Chinese dyslexia assessment tool named Chinese Reading Ability Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…As further confirmation and assist, we conducted a literacy test, called the Chinese Reading Ability Test (CRAT), for the preliminarily diagnosed dyslexia children, with normally developing children from the same classes as controls. The CRAT includes five subscales on Chinese cognitive-linguistic measures of phonological awareness, morphological awareness, rapid automatized naming, orthographic awareness, and reading comprehension [ 23 ], which took about 45 min to complete for each student. There are three tests in the phonological awareness subscale: rhyme identification, onset identification, and tone identification, which are classical tests in the study of dyslexia in Chinese.…”
Section: Methodsmentioning
confidence: 99%
“…As further confirmation and assist, we conducted a literacy test, called the Chinese Reading Ability Test (CRAT), for the preliminarily diagnosed dyslexia children, with normally developing children from the same classes as controls. The CRAT includes five subscales on Chinese cognitive-linguistic measures of phonological awareness, morphological awareness, rapid automatized naming, orthographic awareness, and reading comprehension [ 23 ], which took about 45 min to complete for each student. There are three tests in the phonological awareness subscale: rhyme identification, onset identification, and tone identification, which are classical tests in the study of dyslexia in Chinese.…”
Section: Methodsmentioning
confidence: 99%
“…The CRAT, which has a good reliability and validity (Cronbach’s α = 0.75), was established for auxiliary diagnosis of Chinese dyslexia. It consists of five subscales, respectively the phonological awareness subscale (PA), morphological awareness subscale (MA), rapid automatized naming subscale (RAN), orthographic awareness subscale (OA), and reading ability subscale (RA) [ 28 ]. The PA consists of three subtests measuring onset, rhyme and tone, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria of the case group were consistent with our previous studies [7]. Briefly, we followed the including criteria as: (1) IQ above 80 by the Raven's Standard Progressive Matrices; (2) at least 1 standard deviation below the average level of their actual grade on the Chinese Vocabulary Test and Assessment Scale, which is the widely used reading level test for screening Mandarin-speaking Chinese children for dyslexia (Cronbach's α = 0.75) [25]; (3) according to the reports from their head-teachers, Chinese language test had been below 10% among all children in the same grade for 6 months; (4) there were at least 2 standard deviations above the mean score in the Dyslexia Checklist for Chinese Children (DCCC), which has a good reliability for Chinese dyslexia identification (Cronbach's α = 0.97) [26]; (5) no suspected brain damage, uncorrected sensory impairment, other mental or neurological disorders or any comorbidities (e.g., attention deficit hyperreactivity disorder); (6) child psychiatrists make the final diagnosis according to the diagnostic criteria of the fifth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), combined with the Chinses Reading Ability Test (CRAT), which is used for auxiliary diagnosis (Cronbach's α = 0.75) [27,28]. After a detailed introduction to our study, we invited these children and their parents to fill out questionnaires.…”
Section: Study Participantsmentioning
confidence: 99%
“…The scale is composed of the phonological awareness subscale, the morphological awareness subscale, the rapid automatized naming subscale, the orthographic awareness subscale, the morphological awareness subscale, the rapid automatized naming subscale, the orthographic awareness subscale, and the reading ability subscale. The study examined both the reliability and validity of the CRAT and concluded that the CRAT has adequate reliability and validity (Huang et al, 2020).…”
Section: Content the Current Study Of Cognitive Assessment Of Dyslexiamentioning
confidence: 99%